Peran Jamaah Masjid Kemayoran Surabaya Dalam Peningkatan Infrastruktur dan Pengelolaan Tanah Wakaf, 1950an-1990an - Arisandy, Yuniar Putri; Husain, Sarkawi B. (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
This article discusses the role of the Surabaya Kemayoran Mosque congregation in improving the infrastructure and management of their waqf land. This research uses historical research methods which consist of finding and gathering sources, verification, aufassung, and darstellung. The origins of this mosque came from the results of the compensation given by the Dutch East Indies Government to Muslims because they wanted to demolish the mosque in Surapringgo. However, the grant of land does not have a documents, but only inscription. This mosque then underwent several changes and infrastructure improvements. In addition, the Kemayoran mosque also has a lot of waqf land originating from worshipers. Most of the waqf land is used by residents to be used as residences or businesses with rental status. The rent from the land is used again for the needs of the mosque and funds for improvements. However, because there was no legal document on which to base it, the issue then sparked several problems related to land reform in the 1970s. The worshipers of the mosque took various ways to convince the tenants that there is no connection between waqf land and land reform. Even though many methods have been taken, the tenants are ultimately unwilling to pay any more rental fees, even though the rights to the land and activities on it are still under the auspices of the Kemayoran Mosque.